Reprint of “Genotoxic permanent hair dye precursors p-aminophenol and p-toluenediamine electrochemical oxidation mechanisms and evaluation in biological fluids” - de Souza, João Carlos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Oliveira-Brett, Ana Maria (Elsevier, 2020)
The p-toluenediamine (PTD) and p-aminophenol (PAP), genotoxic precursor agents widely used in permanent hair dyeing formulations, electrochemical mechanisms and evaluation in biological fluids, at a glassy carbon electrode, in a wide pH range, by cyclic, differential pulse, and square wave voltammetry, were investigated. The oxidation of both PTD and PAP is reversible. The PTD two electrons and two protons transfer diffusion-controlled reaction occurs at the molecule nitrogen atoms in the amine groups. Also PAP oxidation is a two electrons and two protons transfer diffusion-controlled reactions, and occur at the nitrogen and oxygen atoms of the molecule amine and hydroxyl groups. An electrochemical oxidation mechanism for PTD and PAP is proposed. The PTD and PAP diffusion coefficients, DPTD = 1.57 × 10−5 cm2 s−1 for PTD, and DPAP = 1.03 × 10−5 cm2 s−1 for PAP, were determined. The electrochemical quantification in 0.10–1.00 μM concentration range showed a detection limit of 0.12 μM for PTD and 0.17 μM PAP. A new electroanalytical method for the determination of PTD and PAP in fetal bovine serum biological fluid, and in artificial urine samples, using differential pulse voltammetry, was also developed.
Keywords: Electrochemical oxidation; Genotoxic precursors; Glassy carbon electrode; Hair dyes; P-aminophenol; P-toluenediamine